2016
DOI: 10.1002/2016jd025053
|View full text |Cite
|
Sign up to set email alerts
|

A potential vorticity‐based index for the East Asian winter monsoon

Abstract: A novel dynamically based index that reflects the strength of the regional potential vorticity (PV) intrusion on the 300 K isentropic surface is proposed as a reliable measure of East Asian winter monsoon (EAWM) intensity. The index captures essential aspects of the EAWM, including its climatic influences on East Asia, its continuous weakening trend since the 1980s, and its close relationships with the Siberian high, Arctic Oscillation, and El Niño. The use of a potential vorticity framework enables the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 39 publications
(50 reference statements)
1
29
0
Order By: Relevance
“…While isentropic surfaces below 300 K (i.e., 280 K and 290 K) may have even tighter coupling to the surface temperature over East Asia, these lower isentropic surfaces intersect the geoid within the East Asian region. Additionally, our use of 300 K isentropic surface allows us to refer directly to the PV‐based EAWMI [ Huang et al , ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While isentropic surfaces below 300 K (i.e., 280 K and 290 K) may have even tighter coupling to the surface temperature over East Asia, these lower isentropic surfaces intersect the geoid within the East Asian region. Additionally, our use of 300 K isentropic surface allows us to refer directly to the PV‐based EAWMI [ Huang et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…Isentropic PV can be calculated as PV=g(ζθ+f)∂θ∂p, where g is the gravitational acceleration, ζ θ is the relative vorticity on the isentropic surface, f is the planetary vorticity (Coriolis parameter), and ∂θ∂p is the quasi‐vertical gradient of potential temperature θ with respect to pressure p . Noting that cold surges over East Asia are reflected in the intensity of the area‐averaged PV over East Asia with respect to the zonal mean, Huang et al [] defined a PV‐based East Asian winter monsoon index (EAWMI) by EAWMI=falsePVnormal300K(90150°normalE,2050°normalN)¯falsePVnormal300K(0360°normalE,2050°normalN)¯. The first term on the right‐hand side of equation is the area‐averaged PV over East Asia (90–150°E, 20–50°N) on the 300 K isentropic surface, while the second term is the area‐averaged PV over the entire 20–50°N latitudinal band on the 300 K isentropic surface. Basing this definition on the isentropic PV permits the application of the invertibility principle of isentropic PV [ Hoskins et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, although the AO index did show an increasing trend during 1950–2000 [ Gong and Drange , ], it experienced a decreasing trend after the mid‐1990s [ Overland and Wang , ; Cohen and Barlow , ; Cohen et al , ]. Moreover, while the EAWM experienced continuous weakening around 1988 [ Watanabe and Nitta , ; Jhun and Lee , ; Wang et al , ; Huang et al , ], there was a recent recovery that began around 2009 [ Wang and Chen , ; Ding et al , ; Huang et al , ]. Therefore, the long‐term trends in the SLP anomalies and surface temperature anomalies are not removed.…”
Section: Methodsmentioning
confidence: 99%
“…First, many previous studies have suggested that March is as important as the time period from December to February when examining the wintertime temperature anomalies over eastern North America [ Wang and Fu , ; Alexander et al , ; Mo and Schemm , ; Notaro et al , ]. Second, Huang et al [], studying the wintertime climate of eastern Asia, considered the intensity of potential vorticity (PV) intrusion from high latitudes into eastern Asia as a means for determining which months should be regarded as climatological winter. They found that the intensity of PV intrusion into eastern Asia in March is comparable in magnitude to that in December and far exceeds the levels seen in November.…”
Section: Methodsmentioning
confidence: 99%